Genomic analyses of the Chlamydia trachomatis core genome show an association between chromosomal genome, plasmid type and disease - Bart Versteeg; Sylvia M. Bruisten; Yvonne Pannekoek; Keith A. Jolley; Martin C. J. Maiden; Arie van der Ende; Odile B. Harrison (BMC Genomics, 2018)
Abstract Background Chlamydia trachomatis (Ct) plasmid has been shown to encode genes essential for infection. We evaluated the population structure of Ct using whole-genome sequence data (WGS). In particular, the relationship between the Ct genome, plasmid and disease was investigated. Results WGS data from 157 Ct isolates deposited in the Chlamydiales pubMLST database (http://pubMLST.org/chlamydiales/) were annotated with 902 genes including the core and accessory genome. Plasmid associated genes were annotated and a plasmid MLST scheme was defined allowing plasmid sequence types to be determined. Plasmid allelic variation was investigated. Phylogenetic relationships were examined using the Genome Comparator tool available in pubMLST. Phylogenetic analyses identified four distinct Ct core genome clusters and six plasmid clusters, with a strong association between the chromosomal genotype and plasmid. This in turn was linked to ompA genovars and disease phenotype. Horizontal genetic transfer of plasmids was observed for three urogenital-associated isolates, which possessed plasmids more commonly found in isolates resulting from ocular infections. The pgp3 gene was identified as the most polymorphic plasmid gene and pgp4 was the most conserved. Conclusion A strong association between chromosomal genome, plasmid type and disease was observed, consistent with previous studies. This suggests co-evolution of the Ct chromosome and their plasmids, but we confirmed that plasmid transfer can occur between isolates. These data provide a better understanding of the genetic diversity occurring across the Ct genome in association with the plasmid content.